Numerical methods in the hydrological sciences - Hornberger, George M.; Wiberg, P. L. (Patricia L.) ([Washington, DC] : American Geophysical Union, 2005)
This electronic book provides students, instructors and professionals in the hydrological sciences the tools they need to pursue study and research using numerical methods. It will enable them to write programs to solve fairly complex problems, to explore and understand the current literature in which numerical methods are used, and to have the confidence to delve into texts on numerical methods to extend their knowledge to solve new problems.
Title from HTML table of contents page (viewed on Sept. 28, 2009).
Includes bibliographical references and index.
Keywords: Hydrology -- Mathematical models; Hydrology -- Mathematical models; Electronic books